Development of an EOG-based system to control a serious game. (October 2018) - López, Alberto; Fernández, Marta; Rodríguez, Héctor; Ferrero, Francisco; Postolache, Octavian
Graphical abstract: Highlights: To develop an EOG-based system to control a serious game. To develop a low-cost hardware device to wirelessly transmit the EOG signals to the computer. To train the oculomotor system of people with motor disabilities. To show the advantages and disadvantages of EOG-based systems. Abstract: Eye movements are the least affected by disabilities of the central motor system. This means that eye movements have great potential in the development of applications adapted to people with motor disabilities. This article describes the development of an electrooculography (EOG) system to control a serious computer game. The goal is to allow people with motor disabilities to play a serious game and improve control over their oculomotor systems. The developed system consists of three subsystems: a low-cost hardware device to acquire the EOG signals, methods to process them digitally, and a serious game controlled exclusively by eye movements. Fourteen able-bodied volunteers of different ages and genders tested the computer game. The evaluation of the system's interaction capacity with the computer game was based on three metrics: score obtained, number of successful interactions, and number of errors committed.